PENGARUH KEGIATAN FINGER PAINTING TERHADAP PERKEMBANGAN MOTORIK HALUS ANAK USIA 5-6 TAHUN DI TK GKPI TARUTUNG KOTA - Devita Siregar; Emmi Silvia Herlina; Mei Lastri E.F Butar-butar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Research is to determine the effect of finger painting activities on the fine motor development of children aged 5-6 years at TK GKPI Tarutung City. The research hypothesis is: "There is a significant effect of finger painting activities on the fine motor development of children aged 5-6 years at TK GKPI Tarutung City." The population consists of all children aged 5-6 years at TK GKPI Tarutung City, totaling 113 individuals. The research sample was determined using a non-probability sampling technique, namely students from classes B1, B4, and B5 totaling 60 students as the experimental class using finger painting activities, and classes B2 and B3 totaling 53 students as the control class using the usual treatment (conventional class). The research method used is an experimental design with a Quasi-Experimental method in the form of a Nonequivalent Control Group Design. The instrument used in this study is a questionnaire consisting of 15 items. The research data for the questionnaire were analyzed using the average difference test formula (N-Gain Score). It was found that the average score for the experimental class was 0.7163, which falls into the high category. The average score for the control class was 0.3371, which falls into the moderate category. Then, an independent test using the t-test was conducted, yielding a t-value of 10.419 > t-table(α=0.05; df=111) = 1.980. Thus, it can be concluded that the research hypothesis is accepted, indicating a significant influence of finger painting activities on the fine motor development of children aged 5–6 years at TK GKPI Tarutung City, and H0 is rejected.